PENGARUH LATIHAN CORE STABILITY TERHADAP KESEIMBANGAN DINAMIS DAN KECEPATAN TENDANGAN ANGGOTA PENCAK SILAT SMP NEGERI 35 BEKASI - Nia Kurniawati; Gina Dyo Salsabila; Erna Sariana (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2021)
Background: Pencak Silat is one of a martial arts which defined as self-defense skills. Physical performance which an important roles in Pencak Silat’s player is dynamic balance. Kick is a dominant technique, kick speed of Pencak Silat’s player is important and particular concern during training. Core stability exercise have to improving core muscle and skill performance level. Purpose: The study analyzed the effect of core stability training on dynamic balance and kick speed in pencak silat members. Method: Design that used in this research is pre-experimental with one group pretest-posttest. This research was conducted at SMPN 35 Bekasi and lasted for 4 weeks. Research population was all members of Pencak Silat extracurricular, the sample was taken by purposive sampling with 13 participants. Dynamic balance measurements were performed with a modified bass test and speed of kick in pre-intervention and post-intervention. Results: showing that p-value 0.000 (p<0.005) which means it has an effect of core stability exercise to dynamic balance and speed of kick in Pencak Silat’s members at SMPN 35 Bekasi.